(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of recreational and tourist resources of the Kashkadarya region. The main attention is paid to the development of tourism and recreation in Kashkadarya, the expansion of the recreational and tourist influx, the effectiveness of the use of historical, cultural monuments, recreational and recreational attractions.